Overview of the Effect of Family Support on Anxiety in Pregnant Women at Duren Sawit Hospital - Fadillah, Helga Putri; Abriya, Witri (Green Publisher Indonesia, 2026)
Pregnancy is a period that is prone to anxiety due to physical, hormonal, and psychological changes experienced by pregnant women, which can have an impact on the health of the mother and fetal development if not handled properly. One of the factors that plays a role in reducing anxiety levels is family support, both in emotional, informational, and instrumental forms. This study aims to determine the effect of family support on the anxiety levels of pregnant women at Duren Sawit Hospital. The research method used is a quantitative approach, with the measurement of family support using the Multidimensional Scale of Perceived Social Support (MSPSS) instrument, which has been tested for validity and reliability in various contexts, including among pregnant women in Indonesia, with a Cronbach’s alpha value of > 0.85. The results showed that most respondents were in the optimal reproductive age group, predominantly primipara, and mostly in the first and second trimesters of pregnancy. Most respondents also had high family support. Statistical analysis showed that there was a tendency for higher family support to be associated with lower anxiety levels. However, the relationship between gestational age (trimester) and anxiety level was not statistically significant (p > 0.05), indicating that trimester was not significantly associated with anxiety. Thus, family support plays an important role in reducing anxiety among pregnant women, although it is not the only factor influencing anxiety levels.